Bone-Subtracted Spinal CT Angiography Using Nonrigid Registration for Better Visualization of Arterial Feeders in Spinal Arteriovenous Fistulas - Nishii, T. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Pretreatment diagnosis for the location of shunts and arterial feeders of spinal arteriovenous fistulas is crucial. This study aimed to evaluate the utility of subtracted CT angiography imaging by using nonrigid registration (R-CTA) in patients with spinal arteriovenous fistulas compared with conventional CTA imaging. MATERIALS AND METHODS: The records of 15 consecutive subjects (mean age, 65 years; 2 women) who had undergone CTA and digital subtraction angiography for clinically suspected spinal arteriovenous fistula were reviewed. From CTA images obtained at the arterial and late arterial phases, warped images of the late arterial phase were obtained by using nonrigid registration that was adjusted to the arterial phase images. R-CTA images were then obtained by subtracting the warped images from the arterial phase images. The accuracies of using nonrigid registration and conventional spinal CTA and the time required for detecting arterial feeders in spinal arteriovenous fistulas were analyzed for each patient with DSA results as a standard reference. The difference between R-CTA and conventional spinal CTA was assessed by the Welch test and the McNemar χ(2) test. RESULTS: R-CTA had a higher accuracy compared with conventional spinal CTA (80% versus 47%, P = .025). The time for interpretation was reduced in R-CTA compared with conventional spinal CTA (45.1 versus 97.1 seconds, P = .002). CONCLUSIONS: Our subtracted CTA imaging by using nonrigid registration detects feeders of spinal arteriovenous fistulas more accurately and quickly than conventional CTA.